Analysis of Difficulties and Strategies in Learning of Visually Impaired Students in West Kalimantan - Venny Karolina; Yusawinur Barella; Hadi Wiyono; Khairunnisa Khairunnisa; Daud Fiqo Ghafika (Edumaspul: Jurnal Pendidikan, 2022)
This study explored the learning strategies and difficulties of visually impaired students. The study involved four students with visual impairment in Pontianak, West Kalimantan Province. The researchers collected data through semi-structured interviews. A qualitative approach was employed in this study. Four informant students took part in this study. All of them were in their secondary education level. The researchers coded the transcription of the interviews. The results showed that visually impaired students preferred to use auditory learning resources and active learning strategies. They perceived these two learning strategies as essential to help them understand the learning materials. Besides, the informant students also claimed that their reading comprehension, self-efficacy and confidence were low. These ideas may facilitate educators to understand what visually impaired students need in their learning and help educators accommodate their teaching in line with what blind students require.